Productividad de las organizaciones basada en Sistemas de Gestión de Información (SGI) en el entorno Colombiano (2015)
"It is very important to make clear from the beginning that there are currently internationally recognized methodologies for Advanced Enterprise Architecture, such as the methodology of TOGAF, Zachman and e-TOM (Sessions, 2007). The methodology Productivity in Organizations based on SGI3 seeks to complement this type of methodologies by using practical tools through the development of workshops and exercises applied from the theories seen in the Master's, my studies in Business Administration and my professional experience as a teacher in Information Systems in organizations in the Colombian environment. The Master in Information Management is the first interdisciplinary program that seeks the advanced development of knowledge and skills of both systems engineers and administrators and related professionals, to achieve consistency between business strategies and Information Technology. (IT) in organizations. This integrates business processes and IT services that generate competitive advantages in order to substantially improve the positioning of the organization in its natural market (GARAVITO, 2011) ... "- Extract of the document